Diseño y desarrollo de un desinfectante para pisos a base del aceite esencial de Palo Santo (Bursera graveolens) - Bravo Arias, Olga Fabiola (2014)
The aim of this study was to apply the essential oil of palo santo (Bursera graveolens) as a disinfectant. To determine the compatibility active principle – excipients through of a period time study was performed based on the factorial Plackett and Burman. The essential oil valuation of was performed by GC-MS. The study of the physico-chemical and microbiological characteristics were performed during the six-month stability study, where the variations were observed in the color, pH, and concentration of the active principle. The biological activity of the product was performed using the broth microdilution assay. The results showed inhibition at concentrations less than 1000 ppm even in the sample free of active ingredient against to Pseudomonas aeruginosa, Staphylococcus aureus, Trichophyton rubrum and Trichophyton mentagrophytes.